Analysis of the Need for Feeder LRT (Light Rail Transit) Palembang City on Jalan Jendral Ahmad Yani - M. Hijrah Agung Sarwandy; Jonizar (PT FORMOSA CENDEKIA GLOBAL, 2023)
Application of a feeder transportation system that connects direct access to the LRT to provide convenience for people who use private vehicles to switch to using public transportation modes. Therefore the purpose of this study is to analyze the need for LRT feeder transport on the Jalan Jendral Ahmad Yani section to support ease of access using the LRT service. The analysis in this study used descriptive statistical methods obtained from survey data which were grouped based on movement characteristics, opinions on LRT modes of transportation and the level of need for feeder transport on Jalan Jendral Ahmad Yani. survey method by way of direct interviews (face to face) using questionnaires to obtain primary data which will later be processed to obtain the desired data. Based on the data obtained, the results of the analysis show that the characteristics of movement in the study area are studying and working. Perceptions of the LRT mode of transportation found that the LRT mode of transportation has not become the main choice as transportation for carrying out daily activities